Passively Q-switched Erbium-Doped Fibre Laser Based on Graphene-Chitin Saturable Absorber - Rashid, Nur Nadhirah Mohamad; Lokman, Muhammad Quisar; Zuikafly, Siti Nur Fatin; Nordin, Nur Azmah; Yahaya, Hafizal; Ismail, Mohammad Faizal; Harith, Ahmad; Wan Nawawi, Wan Mohd Fazli; Fauzan, Ahmad (Penerbit Akademia Baru, 2023)
Graphene is a carbon allotrope composed of densely packed sp2-assembled carbon atoms in a honeycomb-like crystal lattice. It is widely used in various fields of materials science to develop sensors, optoelectronic devices, nanocomposites, and others due to its excellent electronic, mechanical, optical, and thermal properties. Graphene offers several advantages, including ease of fabrication, ultrafast recovery times, low fabrication cost, and low saturation intensities. Its unique zero bandgap property makes it the only material with wavelength-independent absorption, which is advantageous in generating pulsed lasers using saturable absorbers. This study investigates the performance of graphene with a chitin bio-host polymer as a saturable absorber in a 1.5 μm erbium-doped fibre laser. Graphene embedded in chitin was fabricated and utilized in a pulsed laser cavity operating in the wavelength region of 1.5 μm to enable Q-switched pulsed laser operation. The study achieved a pulse energy of approximately 19.83 nJ and a peak power of 10.72 mW. Increasing the pump power from 30.67 mW to 174.28 mW resulted in the highest repetition rate of 63.40 kHz, corresponding to the shortest pulse width of 1.74 μs. These findings have significant implications for applications requiring ultrafast precision and accuracy, such as medical laser equipment and flexible sensors.